Identifying and sourcing pyrometamorphic artifacts: Clinker in subarctic North America and the hunter-gatherer response to a Late Holocene volcanic eruption. (February 2019) - Kristensen, Todd J.; Andrews, Thomas D.; MacKay, Glen; Gotthardt, Ruth; Lynch, Sean C.; Duke, M. John M.; Locock, Andrew J.; Ives, John W.
Abstract: Pyrometamorphic rocks produced by natural coal combustion appear at archaeological sites across North America but have received little archaeological attention regarding provenance studies. Tertiary Hills Clinker is a distinct pyrometamorphic rock from Subarctic Canada utilized by hunter-gatherers from 10, 000 years ago to European contact. We employ X-ray diffraction, thin section analyses, and electron probe microanalyses to characterise Tertiary Hills Clinker and inform archaeometric studies of rock produced by combustion metamorphism. We geochemically compare pyrometamorphic rocks used by pre-contact people across North America to demonstrate that Tertiary Hills Clinker can be sourced using portable X-ray fluorescence. Results indicate that Late Pleistocene/Early Holocene exchange networks in North America were larger than previously thought. A later change in the distribution of Tertiary Hills Clinker may relate to a Late Holocene volcanic eruption (White River Ash east) that fragmented modes of lithic exchange and associated social networks with potential stimulus for a subsequent large-scale migration of northern hunter-gatherers across the continent. Provenance studies of pyrometamorphic artifacts offer untapped opportunities to study social networks in coal-bearing regions across the world. Highlights: Clinkers are pyrometamorphic rocks fused by natural coal combustion. Vitreous clinkers were used across North America for pre-contact tool production. Clinker artifacts can be sourced to outcrops using portable x-ray fluorescence. Tertiary Hills Clinker (THC) artifacts spread over 1.25 million km 2 across Canada. Changes in THC distribution suggest that a volcanic eruption severed social networks.